Equity, diversity, and inclusion in developmental neuroscience: Practical lessons from community-based participatory research - La Scala, Shayna; Mullins, Jordan L.; Firat, Rengin B.; , Emotional Learning Research Community Advisory Board; Michalska, Kalina J. (Frontiers in Integrative Neuroscience, 2023)
Exclusion of racialized minorities in neuroscience directly harms communities and potentially leads to biased prevention and intervention approaches. As magnetic resonance imaging (MRI) and other neuroscientific techniques offer progressive insights into the neurobiological underpinnings of mental health research agendas, it is incumbent on us as researchers to pay careful attention to issues of diversity and representation as they apply in neuroscience research. Discussions around these issues are based largely on scholarly expert opinion without actually involving the community under study. In contrast, community-engaged approaches, specifically Community-Based Participatory Research (CBPR), actively involve the population of interest in the research process and require collaboration and trust between community partners and researchers. This paper outlines a community-engaged neuroscience approach for the development of our developmental neuroscience study on mental health outcomes in preadolescent Latina youth. We focus on ‘positionality’ (the multiple social positions researchers and the community members hold) and ‘reflexivity’ (the ways these positions affect the research process) as conceptual tools from social sciences and humanities. We propose that integrating two unique tools: a positionality map and Community Advisory Board (CAB) into a CBPR framework can counter the biases in human neuroscience research by making often invisible–or taken for granted-power dynamics visible and bolstering equitable participation of diverse communities in scientific research. We discuss the benefits and challenges of incorporating a CBPR method in neuroscience research with an illustrative example of a CAB from our lab, and highlight key generalizable considerations in research design, implementation, and dissemination that we hope are useful for scholars wishing to take similar approaches.